PENGARUH KINERJA ORGANISASI SANTRI PUTRI (OSPI) TERHADAP KEDISIPLINAN SANTRI KELAS 3 PUTRI PONDOK PESANTREN NURUL IMAN AL-HASANAH LEUWILIANG BOGOR - Siti Maesaroh; Ahmad Idhofi; Milahtul Latifah; Djunawir Syafar (Jurnal Manajemen Pendidikan Islam Al-Munadzomah, 2024)
The development of formal education has encouraged some pesantren to improve their management. One sign of this progress is the establishment of the Santri Organization as a platform for kepesantrenan activities. The purpose of this study aims to understand the performance of the Santri Putri Organization (OSPI), the discipline of students, and the influence of OSPI performance on the discipline of grade 3 students at Nurul Iman Al-Hasanah Islamic Boarding School. This research method uses descriptive quantitative methods. Conducted from March to April 2023 at the Islamic Boarding School involving 45 respondents. Data was collected through questionnaires and documentation. Data analysis was performed using descriptive analysis and inferential statistics. The results showed a significant correlation between organizational performance and student discipline. The analysis also showed that organizational performance contributed 35.0% to student discipline. Conclusion Overall, the results showed that the performance of the student organization had a significant influence on the discipline of the students in the Islamic Boarding School.